Poverty and deprivation in urban India - Ali, Sabir (ed.) (New Delhi, 2007)
The book describes about the trends, issues and policies, approaches, effect of urban poverty on women, access to basic services, and shelter in India in detail. It attempts to identify workable, practical measures to manage urban poverty effectively.
Keywords: Urban poverty